The Evaluation Of English Textbook Entitled "English For Elementary Students 4" Published By Grahadi Publisher - Aminah, Siti Khalimatul; , Drs. H. Djoko Srijono, M.Hum; , Dra. Dwi Haryanti, M.Hum (2013)
This research paper is mainly intended to find out whether the English textbook used for the fourth year students of Elementary School entitled English for Elementary Students 4 is compatible or not with the indicators of good materials design suggested by Sundara Rajan. This research applies descriptive research. In collecting data, the writer used documentary analysis as the instrument. The data were analyzed by steps; (1) presenting the materials (2) comparing the materials (3) judging whether the materials of English textbook appropriate with the indicators of good materials design suggested by Sundara Rajan or not (4) drawing conclusions. The result of the analysis shows that the percentage of the compatibility of the language skills developed in the textbook is 59,09 %. It means the textbook is good in developing language skills materials as suggested by Rajan.the language skills which are developed in the textbook involve: the compatibility of the listening materials are 63,63% or good, the compatibility of the reading materials are 63,63 or good, the compatibility of speaking materials are 63,63% or good and the compatibility of writing materials are 45,45% or fair. This research implies the textbook entitled "English for Elementary Students 4" for the fourth year students of Elementary School is good materials to support the learning process. The materials of writing skill in the textbook is not adequate, so the other materials in needed to support the writing teaching-learning process